Efektivitas LKS Berbasis KPS Asam-Basa dalam Meningkatkan KPS Siswa Laki-laki dan Perempuan - Adi Ariska; Noor Fadiawati; Nina Kadaritna (Universitas Lampung, 2018)
This research was aimed to describe the effectiveness of students worksheets in improving students science process skills (SPS) of male and female students. The 2x2 factorial design was used in this research. The population in this research were students of class XI science at SMAN 16 Bandar Lampung on academic year 2016-2017. The sample in this research were students of class XI science 4 and XI science 6 that was taken by purposive sampling technique. The instrument in this research were student worksheet based on SPS and conventional, pretes and postest questions and attitude assessment sheet. Two ways ANOVA test and t test were used as data analysis technique. The results showed that SPS based on students worksheets effective in improving students SPS of male and female students compared to conventional students worksheets. There was no interaction between learning by students worksheets and gender to SPS.Penelitian ini bertujuan mendeskripsikan efektivitas LKS dalam meningkatkan keterampilan proses sains (KPS) siswa laki-laki dan perempuan. Desain penelitian yang digunakan dalam penelitian ini adalah desain faktorial 2x2. Populasi dalam penelitian ini adalah siswa kelas XI IPA di SMAN 16 Bandar Lampung tahun pelajaran 2016-2017. Sampel dalam penelitian ini adalah siswa kelas XI IPA 4 dan XI IPA 6 yang diperoleh melalui teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah LKS berbasis KPS dan konvensional, soal pretes dan postes, serta lembar penilaian sikap. Teknik analisis data yang digunakan adalah ANOVA dua jalur dan uji t . Hasil penelitian menunjukkan bahwa LKS berbasis KPS efektif dalam meningkatkan KPS siswa laki-laki dan perempuan dibandingkan dengan LKS konvensional. Tidak terdapat interaksi antara pembelajaran menggunakan LKS dengan jenis kelamin terhadap KPS siswa.Kata kunci: asam-basa, jenis kelamin siswa, KPS, LKS